EVALUATION OF THE BIOMASS PRODUCTION OF THE MAIN STEM OF A HYBRID EUCALYPTUS CLONE UNDER DIFFERENT SPACINGS - Santos Barzotto Ribeiro, Maria Dolores dos [UNESP]; Blanco Jorge, Luiz Alberto [UNESP]; Mischan, Martha Maria [UNESP]; Dos Santos, Andre Luis; Ballarin, Adriano Wagner [UNESP] (Centro Pesquisas Florestais, Ufsm, 2017)
The use of forests of Eucalyptus has become more expressive in Brazil, mostly because of the excellent production in volumetric terms reached by them and the good characteristics of the obtained wood. The present work was developed to search the best plantations spacings for clonal forests of a interspecific hybrid of Eucalyptus grandis and Eucalyptus urophylla, to maximize the production of the stem biomass per hectare. The data were made available by the company 'Duratex Florestal' and are proceeding from a clonal test at the age of 72 months. The used statistician delineation was the systematic one with continuous quantitative factor, 16 treatments and 40 repetitions, considering that the variation between the treatments was the spacing between the trees and the space between rows was constant with three meters. Along with this arrangement, the vital area per tree was 1,50m(2) (6.667 trees per hectare) to 15,75m(2) (635 trees per hectare). The highest production volume and stem biomass per hectare occurred in spacing treatments with dense planting - 3x0, 50m, in large spacings (from 9.00 m(2) per plant life), it was on volume and biomass per tree stem. In this study, it was observed an increase in the weighted basic density of timber to the vital area of 4.95 m(2) per tree. From this vital area, the basic density remained virtually unchanged.
Keywords: plantations spacing; Eucalyptus clone; stem biomass; systematic design